Silica gel multilayer desiccant hollow cylinder bed for axial flow dehumidification adsorption operations - Nasir, Mohammad Nazmi Mohammad (Universiti Sains Malaysia, 2019)
Energy consumption is increasing gradually every year. It is caused by the growth of air conditioning need in response to higher summer temperature resulted from climate changes. Consequently, this causes an increase in electricity demand. Solar cooling is a relatively new, reliable and clean energy application of proven refrigeration technology that able to improve comfort conditions. This technology also limits the impact on the environment and conserves energy. The main element in desiccant cooling system is the desiccator. In this study, single and two layer hollow test bed were made. The adsorption ability of silica gels as the solid desiccant materials also tested under varied inlet air velocity (1.0 m/s, 1.2m/s, 1.5 m/s, 2.15 m/s, 3.7m/s and 4.9 m/s. The result show that increase in inlet air velocity value cause reduction in adsorption rate of the desiccant bed. This trend can be seen for both single and double layer desiccant bed experiment. However, the experimental setup requires a stable humidification capability for the adsorption experiment. Mist spray method has been selected to be used in the humidity addition system. The performance of 4 and 9 numbers of nozzles under vertical, parallel and counter flow arrangement have been analysed for air velocity from 1 m/s to 6.2 m/s, relative humidity between 59% and 78% and room temperature from 28.5 ˚C to 30.2 ˚C. The data shows that the humidification effect is directly proportional to the number of nozzle. The highest relative humidity is recorded at 88.4% in 9 numbers of nozzle use under vertical flow. The performances of vertical and counter flow are further tested with nozzle arrangement of 2, 4, 6 and 8. The data collected show that highest relative produce was by 8 nozzles under vertical flow at 89.8%.